Lifestyle and psychosocial factors in inflammatory bowel disease: Prevalence, impact, motivation, and support needs - Karlijn Demers; Evelien M. B. Hendrix; Ashkan Rezazadeh Ardabili; Quirine M. Bredero; Ad A. van Bodegraven; Daniëlle van der Horst; Daisy M. A. E. Jonkers; Merel L. Kimman; Zlatan Mujagic; Mariëlle J. Romberg-Camps; Tessa E. H. Römkens; Menne P. Scherpenzeel; et al. (PLoS ONE, 2025)
Background and aim Lifestyle and psychosocial factors impact mucosal inflammation and well-being of Inflammatory Bowel Disease (IBD) patients. However, lifestyle assessment and interventions are not standard care. The aim of this study was to estimate the occurrence of and gather patients’ perspectives on unfavorable lifestyle and psychosocial factors in individuals with IBD. Methods A multicenter study was conducted, enrolling IBD patients using a telemedicine platform that reports on disease activity, lifestyle, and psychosocial factors. Patients' perspectives were gathered through a nationwide online survey distributed by the Dutch IBD patient organization. Results In the telemedicine cohort (n = 460), 16.3% followed a specific diet, and 50.7% believed diet impacted their disease or quality of life. Additionally, 67.4% did not meet exercise norms, 9.3% smoked, and 8.0% had excessive alcohol consumption (>7 units/week). About one-third experienced high stress, poor sleep regularly, and emotional distress occasionally. In the nationwide survey (n = 1126), most patients (58–91%) believed that stress, unhealthy diet, poor sleep, physical inactivity, and anxiety or depression could cause intestinal symptoms. Around 70% were motivated to change diet, stress management, and physical activity. Less than one-fifth of patients received hospital support, with the majority being satisfied. Approximately 20% of patients desired but lacked support concerning stress, physical activity, diet, and sleep. Conclusions Patients with IBD commonly report unfavorable lifestyle and psychosocial factors, recognize their impact on intestinal symptoms, and are motivated to change, but often lack hospital support. This underscores the importance for systematic incorporation of lifestyle and psychosocial factors into patient-centered IBD care and the potential for targeted interventions.